Impact of Drugs Effective for Neuropathic Pain on the Frequency of Hospitalization, Debridement and Amputation Need in Patients with Diabetic Foot Infection - Tanir, Busra; Ugur, Kader; Kurt, Osman; Balin, Safak Ozer (Doc Design Informatics Co Ltd, 2024)
Objective: This study aimed to investigate the impact of drugs used in the treatment of diabetic neuropathy on the frequency of hospitalization, need for debridement and amputation. Methods: One hundred forty-four patients who received inpatient treatment for diabetic foot infection between 2017 and 2020 were analyzed retrospectively through patient files. Patients without diabetic neuropathy were defined as Group 0, those with diabetic neuropathy who used drugs for diabetic neuropathy as Group 1, and those who did not use drugs for diabetic neuropathy were defined as Group 2. The groups were compared in terms of age, height, weight, gender, comorbidities, time elapsed after diabetes mellitus diagnosis and diabetic neuropathy, quantity of diabetic foot attacks, hospitalizations due to diabetic foot infection, need and quantity of debridement and amputation. Results: The time since diagnosis of diabetes mellitus, the rate of insulin use, and hospitalizations due to diabetic foot infection were higher in patients with diabetic neuropathy compared with patients without neuropathy (p=0.01, p=0.02, p=0.024). The difference between Groups 1 and 2 in terms of diabetic foot infection attacks, hospitalizations and debridement needs was statistically significant (p=0.039, p=0.02, p=0.06). When comparing whether or not debridement or amputation was required due to diabetic foot infection and the number of amputations, there was no statistically significant difference between the groups. Conclusions: The results of our study suggest that although the use of medications effective for neuropathic pain does not significantly affect amputation due to diabetic foot, it has a protective effect on the number of diabetic foot attacks, the number of hospitalizations due to diabetic foot, and the number of debridement needs.
Diyabetik Ayak İnfeksiyonu Olan Hastalarda Nöropatik Ağrıya Etkili İlaç Kullanımının Hastaneye Yatış Sıklığı, Debridman ve Ampütasyon İhtiyacı Üzerine Etkisi
Keywords: diabetic foot; infection; neuropathy; hospitalization; amputation